2013
DOI: 10.1161/strokeaha.113.001219
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Vertebral Artery Occlusion

Abstract: Background and Purpose-To elucidate the mechanisms and prognosis of rotational vertebral artery occlusion (RVAO). Methods-We analyzed clinical and radiological characteristics, patterns of induced nystagmus, and outcome in 21 patients (13 men, aged 29-77 years) with RVAO documented by dynamic cerebral angiography during an 8-year period at 3 University Hospitals in Korea. The follow-up periods ranged from 5 to 91 months (median, 37.5 months). Most patients (n=19; 90.5%) received conservative treatments. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 38 publications
1
37
0
2
Order By: Relevance
“…Perhaps a large follow-up study using these criteria that compares participants with significant PN with healthy participants would provide useful insight into not-yet-detected vestibular lesions. This study should separately evaluate horizontal, vertical, and oblique nystagmus; analyze several aspects of the nystagmus; test the criteria against a gold standard such as MRI and/or cerebral angiography; and use the fixation index when nystagmus is observed (Bertholon et al, 2002;Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps a large follow-up study using these criteria that compares participants with significant PN with healthy participants would provide useful insight into not-yet-detected vestibular lesions. This study should separately evaluate horizontal, vertical, and oblique nystagmus; analyze several aspects of the nystagmus; test the criteria against a gold standard such as MRI and/or cerebral angiography; and use the fixation index when nystagmus is observed (Bertholon et al, 2002;Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al [50] analyzed the outcome of 21 patients diagnosed with rotational VA occlusion (RVAO) with a median follow-up period of 37.5 months, and most of them received conservative treatment, except for 2 cases who received C1-C2 fusion. None of the 19 patients under conservative treatment developed posterior circulation stroke, and 4 of them showed resolution of the symptoms during the follow-up, possibly because of spontaneous resolution of the extrinsic compression or central adaptation.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…None of the 19 patients under conservative treatment developed posterior circulation stroke, and 4 of them showed resolution of the symptoms during the follow-up, possibly because of spontaneous resolution of the extrinsic compression or central adaptation. This suggests that conservative treatments might be safe and might be considered as a first-line treatment in RVAO [50]. However, a different conclusion has been drawn in another analysis, which revealed that surgery was associated with a higher favorable outcome, where only 37% of the patients who received a conservative approach had favorable outcomes (p < 0.0001) [3].…”
Section: Treatment Methodsmentioning
confidence: 99%
“…1) It is generally associated with hemodynamic changes, often leading to vertigo and faintness. 2) This condition sometimes causes artery-to-artery embolism due to endothelial damage by osseous process or thick fibrous band surrounding the VA at occipital/C1 or C1/C2, which is called Bow hunter’s stroke. 310) We herein present an extremely rare case showing Bow hunter’s stroke due to stretching and sliding of the VA fenestration between C1 and C2, and discuss its clinical implications with a literature review.…”
Section: Introductionmentioning
confidence: 99%